Screening of postoperative cerebral hyperperfusion syndrome in moyamoya disease: a three-dimensional pulsed arterial-spin labeling magnetic resonance imaging approach - Gao, Feng; Cong, Jianhua; Duan, Yu; Zhao, Wei; Zhu, Zhenfang; Zheng, Yu; Jin, Liang; Ji, Ming; Li, Ming (Frontiers in Neuroscience, 2023)
Introduction Moyamoya disease (MMD) is associated with a risk of postoperative cerebral hyperperfusion syndrome (CHS) after revascularization surgery. This study aimed to explore the feasibility of using three-dimensional pulsed arterial spin labeling (3D PASL) and phase contrast (PC) magnetic resonance imaging (MRI) for predicting CHS occurrence in patients with MMD before revascularization surgery. Methods Overall, 191 adult patients (207 hemispheres) with MMD who underwent combined revascularization surgery were included in this study. Preoperative 3D PASL-MRI and PC-MRI were performed before surgery. The PASL-MRI data were analyzed using SPM12. Patient clinical information, average flow, and preoperative cerebral blood flow (CBF) were compared between the non-CHS and CHS groups. Results Among the patients, 45 (21.74%) developed CHS after revascularization surgery. No significant differences were noted in age, sex, clinical symptoms, hypertension, diabetes, surgical side, or history of revascularization surgery between the non-CHS and CHS groups. However, the average flow in the superficial temporal artery was significantly lower in the CHS group than in the non-CHS group (p < 0.05). Furthermore, 11 clusters of preoperative CBF values were significantly greater in the CHS group than in the non-CHS group [p < 0.05, false discovery rate (FDR) corrected]. A significant correlation was also observed between the preoperative time-to-flight MR angiography (MRA) scores and CBF values in patients with MMD (p < 0.05). Conclusion Compare patients with lower preoperative CBF and higher preoperative average flow in the STA, patients with higher preoperative CBF and lower preoperative average flow in the STA are more likely to develop postoperative CHS Preoperative PASL-MRI and PC-MRI examinations may help to screen patients at high risk of developing CHS after revascularization surgery.